Nutritional profile of triathletes in a week before a national competition - Cunha, N. F.; Silva, J. F.; Costa, T. N. F. (International Journal of Sports Science, 2015)
The aim of this study was to evaluate the nutritional profile of triathletes in the week prior to a triathlon national event. Study participants were 08 triathletes of both sexes, who carried out the 10th edition of SESC-Triathlon National Circuit, Sprint and Olympic, in the city of Palmas, Tocantins, Brazil. The consumption of energy and macronutrients were evaluated by self-report of 03 food records in the previous week of the national competition, in which two should be conducted during the week and on days that had at least one of the modes of triathlon and the third nutrition survey must necessarily be filled in the day before the competition. The body mass found was 72.7kg±11.1 kg. The triathletes energy intake was adequate (31.8±5.5 kcal.kg-1/day), whereas there was a low carbohydrate intake to 75% of participants, with an average consumption of 4.6±0.9 g.kg-1/day. The protein intake remained within the recommendation (1.3±0.2 g.kg-1/day) with 62.5% of athletes showing adequacy. The fat intake has remained above recommended levels, with an average intake of 2.9±0.5g.kg-1/day. The elevated intake of this nutrient was seen occur in 37.5% of participants. It could be concluded that athletes have nutritional inadequacies and that consumption of carbohydrate in the days preceding the exercise was not correlated to the competition time for the athletes evaluated.